Pengaruh Pengetahuan, Persepsi, dan Sikap Terhadap Minat Beli Rumah Berkonsep Urban Farming Makassar: The Effect of Consumer Knowledge, Perceptions, and Attitudes On Intentions To Buy A House With an Urban Farming Concept In Makassar City - Zulfikar, Zulfikar; Muflikhati, Istiqlaliyah; Johan, Irni Rahmayani (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
The large number of residential properties makes market competition increase. Many factors can influence consumer behavior before deciding to buy a product. The level of knowledge, perceptions, and attitudes can be factors that can influence consumer intentions to buy housing with the urban farming concept. This study aims to analyze the effect of knowledge, perceptions and attitudes on the intention to buy a house with the concept of urban farming. The scope of discussion in this study is limited to the influence of demographic characteristics, knowledge, perceptions, and attitude variables regarding the models and benefits of urban farming and the interest in buying residential real estate in the city of Makassar. The data analysis method used is a quantitative method. The collected data is processed using SPSS (Statistical Program for Social Science) and SEM (Structural Equation Modeling) analysis tools with the PLS (Partial Least Squares) approach. The results obtained were 202 respondents and showed that the knowledge variable did not have a significant effect on consumer interest in buying a house with the urban farming concept. However, if it is mediated by attitude and perception variables, the result is that knowledge variables indirectly affect consumer interest. Perception and attitude variables have a significant direct effect on consumer buying interest. The results of the study also show that high prices will affect consumer buying interest. The managerial implication of this research is that developers can use the results of this research to develop their marketing strategies to attract consumers to buy houses. Keywords: intention to buy, knowledge, perceptions, attitudes, urban farming